РОЛЬ ОБ’ЄДНАНИХ ТЕРИТОРІАЛЬНИХ ГРОМАД У НОВІЙ КОНФІГУРАЦІЇ ЕКОНОМІКИ РЕГІОНАЛЬНОГО ПРОСТОРУ - Gudz, P.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2018)
The author’s interpretation of the essence of space and economy of the regional space is given in the article. The regional economic space is treated as the aggregate of industrial relations of the population in the system of constraints on physical parameters (time, air, water, land, mineral resources) — extra-territorial, which interacts with objects of natural and material culture for conducting economic activity on the principles of organization and manageability. The purpose of the article is to determine the ways of influencing the economy of the united territorial communities (UTC) for the new configuration of the regional space: activation of the local economic space and the local market of goods and services, institutional provision of economic development of communities, integration of communities and actors of local markets, public administration and administration of local and regional economic development. Based on the estimation of the financial capacity of the UTC of the Zaporizhzhya Oblast in 2017, it was concluded that there is a direct correlation between the indicators of population size and its financial capacity, since the aggregate economic potential of a community with a population of more than 5 thousand people is more powerful. It has been proved that in larger communities the higher development of human potential, greater opportunities for local economic development through the involvement of households, family businesses, cooperatives, private firms for business organization, a more powerful demand for products and services of the local market is formed, that is, the effect of the scale of production, which means that prerequisites are created for providing better administrative, public, communal, management services. Proposed to the main ways of realizing the modern mission of UTC include: the activation of local economic space and lo cal market; institutional provision of economic development of UTC; Integration mechanisms of community interaction, which can be implemented in different ways; public management of local and regional development. The use of factual data of economic activity of communities by these methods of action leads to a qualitative modification of the economy of the regional space. The next stage of research will be the definition of the characteristics of the transformed regional economic space, the study of the laws of its development under the influence of the emerging economics of UTC. REFERENCES: 1. Bystriakov I.K., Mantsevych Yu.M. Problemy prostorovoho rozvytku Ukrainy z pozytsii pohliadiv P. Aberkrombi. Ekonomika Ukrainy. 2015. No. 9. S. 39-48 [in Ukrainian].2. Kovbasiuk Yu.V. Novi pidkhody do formuvannia rehionalnoi polityky ta rehionalnoho upravlinnia. Aktualni problemy ekonomiky. 2014. No. 7 (157). S. 246-253 [in Ukrainian].3. Upravlinnia stratehichnym rozvytkom obiednanykh terytorialnykh hromad: innovatsiini pidkhody ta instrumenty. Za zah. ta nauk. red. S.M. Serohina, Yu.P. Sharova. Dnipro, 2016. 276 s. [in Ukrainian].4. Snihova O. Smart-spetsializatsiia ta stupid-realizatsiia. Dzerkalo tyzhnia. 2018. No. 1191. 28 kvitnia — 11 travnia [in Ukrainian].5. Hudz P.V. Ekonomichni problemy rozvytku kurortno-rekreatsiinykh terytorii. IEPD NAN Ukrainy. Donetsk: Iuho-Vostok, Ltd, 2001. 270 s. [in Ukrainian].6. Zaporizka oblasna derzhavna administratsiia. Protses detsentralizatsii koryhuie perspektyvnyi plan formuvannia terytorii hromad. URL: http://www.zoda.gov.ua/news/41749/protses-detsentralizatsiji-koriguje-perspektivniy-planf-ormuvannya-teritoriy-gromad.html [in Ukrainian].7. Tkachuk A. Novi pidkhody rozvytku silskykh terytorii v umovakh detsentralizatsii ta zmin u derzhavnii rehionalnii politytsi. 14.05.2018. URL: https://www.csi.org.ua/articles/novi-pidhody-rozvytku-silskyh-terytorij-v-umovah-detsentralizatsiyi-ta-zminu-derzhavnij-regionalnij-politytsi [in Ukrainian].8. Kaziuk Ya., Ventsel V., Demydenko S., Herasymchuk I. Otsinka finansovoi spromozhnosti 366 obiednanykh terytorialnykh hromad za 2017 rik. Detsentralizatsiia. URL: https://decentralization.gov.ua/uploads/library/file/177/_2017.pdf [in Ukrainian].9. Kooperatyvnyi rukh abo Yak sela zarobliaty mozhut. Detsentralizatsiia. 24.07.2018. URL: https://decentralization.gov.ua/news/9272 [in Ukrainian].10. Spivrobitnytstvo hromad. Podillia obiednuietsia — OTH Vinnychchyny ta Khmelnychchyny pidpysaly Memorandum pro spivpratsiu. Detsentralizatsiia. 25.06.2018. URL:https://decentralization.gov.ua/news/9083 [in Ukrainian].11. Zhytomyr mozhete staty pershym v Ukraini sered oblasnykh tsentriv, yakyi stvoryt OTH. 26.07.2018. URL: http://ztrada.gov.ua/?3398[0]=4567 [in Ukrainian].12. O’Toole L.J., Hanf K.I., Hupe P., Walter J.M. Kickert, Joop F.M. Koppenjan. Managing Implementation Processes in Networks. In book: Managing Complex Networks: Strategies for the Public Sector, 1997. P. 137-151. doi: http://dx.doi.org/10.4135/9781446217658.n813. Yalov D.A. Klasternyi podkhod kak tekhnolohiia upravlenyia rehionalnym ekonomycheskim razvitiem. Kompas promyshlennoi restrukturizatsyi. 2004. No. 2. S. 21-24 [in Russian].